Treatment delay in early-stage oral squamous cell carcinoma and its relation to survival - Semmelmayer, Karl; Moratin, Julius; Horn, Dominik; Pilz, Maximilian; Ristow, Oliver; Hoffmann, Jürgen; Freier, Kolja; Engel, Michael; Freudlsperger, Christian (Journal of cranio-maxillofacial surgery, 2021)
The aim of this study was to investigate the impact of a prolonged treatment delay on survival in patients with primary oral squamous cell carcinoma. The investigators hypothesized that treatment delay affects survival, supposing a poor outcome in patients with prolonged treatment initiation. In addition, a critical treatment delay should be defined. Inclusion criteria were a histopathological diagnosis of primary squamous cell carcinoma of the oral cavity and a surgery-based treatment of the tumor. Patients with a history of previously diagnosed malignancies and patients with distant metastasis at the time of diagnosis were excluded from this protocol. Common clinical and histopathological data were assessed retrospectively. Treatment delay was analyzed for the interval between initial presentation and the date of surgery. A total of 484 patients could be included. Considering early-stage patients, the risk of death increases by 1.8% for each day that the treatment delay is prolonged if all other characteristics do not change (p = 0.0035). In patients with advanced disease, a prolonged treatment delay does not affect the risk of death (p = 0.9134). In terms of progression-free survival, treatment delay tends to be associated with a higher risk of recurrence in early-stage disease, but without being statistically significant (p = 0.0718). For patients with early-stage disease, a treatment delay of 20 days is critical regarding overall survival (p = 0.011). For patients with advanced-stage disease, no significant differences have been observed. As patients with early-stage oral squamous cell carcinoma profit from early treatment initiation, we suggest an acceptable maximum treatment delay of no more than 20 days in the surgical management of these patients.